Effect of Genetic Polymorphism of Bovine β-Casein Variants (A1 and A2) on Yoghurt Characteristics - Bibiana Juan Godoy; Idoia Codina-Torrella; Antonio-José Trujillo Mesa (Foods)
The present study aims to evaluate the physicochemical and sensory characteristics of A2 yoghurts (made with A2A2 β-CN milk), in comparison with Control yoghurts (elaborated from conventional milk, a mixture of A1 and A2 β-CN milk). The pH, acidity, water-holding capacity, spontaneous syneresis, firmness and color of yoghurts were monitored during their cold storage (4 °C) for 35 days. Two independent sensory tests (with expert judges and consumers) were also performed. The A2 yoghurts showed only minor differences in some of their physicochemical and sensory characteristics compared to those made with conventional milk. At specific storage times, the A2 yoghurt exhibited higher levels of acidity, luminosity (L*) and firmness, compared to the Control. No differences were observed in the growth curves of the starter (Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus salivarius subsp. thermophilus) during the yoghurt production, nor in the water-holding capacity or spontaneous syneresis of the two types of gels. Regarding the sensory evaluation of samples, the A2 yoghurts were described as firmer and more adherent (by the expert panel), and brighter and more homogeneous (by the consumers) than the Control. In all cases, both consumers and expert sensory panels showed a preference for the A2 yoghurts. Therefore, these results demonstrate the suitability of A2A2 β-CN milk for producing yoghurts with similar characteristics to those obtained with conventional milk.